MORPHOLOGICAL AND PHYSICAL - CHEMICAL CHARACTERISTICS OF SOIL SETTLEMENTS - Ella N. Sutormina (Наука. Инновации. Технологии, 2022)
The article presents a literature review of studies of human impact on soil cities. Emphasis is placed on the properties of soils partially sealed under artificial surfaces. A description of where the problem of soil sealing, urban planning system. A description of where the problem of soil sealing, urban planning system. Described the chemical composition and gu-mussirovannost urban soils, depending on the duration of sealing. Noted fairly low content heavy metals in soils sealed cities.